Using goal programming approach to solve fuzzy multi-objective linear fractional programming problems - De, P. K.; Deb, Moumita (IEEE International Conference on Computational Intelligence and Computing Research, 2016)
The aims of the article is to the study fuzzy multi-objective linear fractional programming (FMOLFP) problem by using goal programming approach. At first by using Charnes and Cooper transformation, the FMOLFP problem is transformed to fuzzy multi-objective linear programming (FMOLP) problem. The reduced problem is formulated by goal programming approach to find out the solution of FMOLFP problem. By using our proposed GP approach some pareto optimal solution is obtained for the FMOLFP problem. A numerical example is presented to demonstrate our approach.